Knowledge And Perceptions of Nutrition and Weight Among First-Year Medical Students at Sriwijaya University - Mitha Ramadea; Ardesy Melizah Kurniati; Joko Marwoto; Syarif Husin; Wardiansyah Wardiansyah; Syarinta Adenina (Biomedical Journal of Indonesia, 2024)
Introduction. Medical students of Sriwijaya University batch 2019 are new students who don’t have much knowledge about nutrition. In addition, new students also don’t know how to calculate Body Mass Index (BMI) through body height and weight. This study aimed to know the level of nutritional knowledge and the suitability of weight perception among the medical students of Sriwijaya University batch 2019. Methods. Descriptive research with a cross-sectional research design was conducted in Health Clinic UPT of Sriwijaya University and the Faculty of Medicine of Sriwijaya University in September 2019. The sample of this study was all medical students from Sriwijaya University batch 2019 who met the inclusion and exclusion criteria. The data was obtained through direct measurement and filling M-GNKQ questionnaire and weight perception questionnaire online. Results. In this study, 222 students met the inclusion and exclusion criteria, with 74 male students and 148 female students. As many as 70.7% of students have normal nutritional status. The average value of nutrition knowledge is 18.21 (45.5%) with the lowest value 0 and the highest value 32. Of all of the students, only 52.3% can perceive body weight correctly. The rest, as much as 33.3% is exaggerating perception and 14.4% is reducing perception. Conclusion. The knowledge of nutrition among the medical students of Sriwijaya University batch 2019 is still quite low and there are still many students who mistakenly perceive their weight.